(untitled) - Bell, Thomas A. (Kansas, US., 1988)
Shrimps are one of the most commercially important groups of animals harvested and farmed throughout the world. Bringing high prices on the market and the table, the results and yields of farmed species has seen continued growth. Under the Editorship of Bruce Phillips an international team of authors provide exhaustive coverage of these fascinating creatures, stretching from growth and development to management and conservation
Keywords: Penaeidae,Crustacea; Histology,Histology